Information Media about Pain Management for Infants in Ungaran Public Health Center - Saparwati, Mona; Trimawati, Trimawati (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
-